(untitled) (Revista horizonte, 2021)
The research describes the factors that hinder or favor the practice of sports for people with disabilities in the regional selections of Goalball, Rugby in saddle and wheelchair basketball in the ninth region of AraucanÃa. The Â methodology Â used Â correspondsto Â the Â qualitative Â one Â and Â the Â main Â data Â collection Â technique Â was Â the semi-structured Â interview. Â The Â participants Â in Â this Â study Â were; Â 19 Â athletes, Â 5 Â teachers, Â and Â 3 Â parents Â whose children Â have Â physical Â disabilities, Â and Â are Â part Â of Â the Â rugby, Â goalball Â andbasketball Â teams Â of Â the Â Temuco district Â of Â Chile. Â The Â main Â findings Â reveal Â that Â the Â main Â obstacle Â to Â the Â practice Â of Â sports Â for Â people Â with disabilities Â is Â the Â lack Â of Â resources, Â in Â addition, Â a Â finding Â that Â is Â typical Â of Â this Â research Â shows Â us Â that Â the climate Â as Â an Â intervening Â element Â of Â the Â regional Â geographical Â reality Â hinders Â the Â practice Â of Â sports, Â as Â the main Â facilitator, Â the Â motivation Â of Â the Â practitioners Â is Â stated, Â finally, Â it Â is Â stated Â that Â the Â main Â challenge Â is linked to the dissemination of inclusive sports that generate awareness among the population, about the fact that people with disabilities are rare, but , normal.